PENGARUH PEMANFAATAN LIMBAH CAIR PABRIK KELAPA SAWIT TERHADAP KUALITAS AIR PADA LAHAN KELAPA SAWIT PT. PMP DI KABUPATEN MAYBRAT - Kristina Daundi; Markus Heryanto Langsa; Alfhons Daniel Sirampun (Jurnal Natural, 2021)
Palm oil mill effluent (LCPKS) is waste produced from fresh fruit bunches of oil palm. Utilization of LCPKS as liquid fertilizer can help the growth of oil palm plants and increase the production of fresh fruit bunches. The purpose of this study was to determine the characteristics of LCPKS in maturity ponds or contact ponds that will be used as liquid fertilizer in oil palm plantations and the effect of LCPKS on groundwater and surface water quality in plantation areas. Secondary data (results of analysis conducted at PT. MSIP's oil palm plantation, Bengkayang Regency) were used to compare the impact of LCPKS after application. The characterization of LCPKS showed a significant decrease in pollutant levels when compared to the average range of untreated sewage pollutant levels. The BOD level of LCPKS in the final treatment pond was 5270 mg/L (almost meeting the quality standard value of 5000 mg/L) compared to the average level of BOD without treatment (21280 mg/L). The application of LCPKS to land can affect the environment, which has the potential to reduce the quality of ground water and surface water. The decline in water quality is indicated by an increase in the value of the pollution index and the status of water quality.